Phagocytic activity of leukocytes and blood cortisol ratings in athletes prior to and after phytopharmacological correction - Vetosheva, V. I.; Volodin, V. V.; Volodina, S. O. (Theory and Practice of Physical Culture, 2019)
The study found the cortisol rates growing over a training cycle in most of the sample, with the growth more expressed in the Master of Sports subsample; and the lymphocyte rates were found to faster drop in the 30+ years old players. The initial rates of the phagocytic activity of leukocytes were found close to the bottom of the norm. Intense physical stresses were found to increase phagocytic activity of leukocytes to the upper limit of the norm, with the effect more expressed in the 30- year-olds. Decrease in the number of lymphocytes with phagocytic activity of leukocytes growth was found indicative of redistribution of the cell pool in favor of monocytes and neutrophils that tend to grow. phytopharmacological correction using Adasten was tested to increase the activity blood protection system elements with good corrective effects and redistributing the cellular elements under physical stress, with the effect more expressed in the 30- year-olds.